PENERAPAN METODE PAKEM MELALUI MEDIA BLOG UNTUK MENINGKATKAN KETERAMPILAN MENULIS PUISI PADA SISWA KELAS X DI SMA NEGERI 10 BONE - Selviana Putri; Muhammad Dahlan (ALGAZALI INTERNATIONAL JOURNAL EDUCATIONAL RESEARCH, 2020)
Abstract: Application of the PAKEM Method through Blog Media to Improve Poetry Writing Skills in Class X Students of SMA Negeri 10 Bone. This study aims to determine the application of the Pakem method through the blog method in improving poetry writing skills in class X students at SMA Negeri 10 Bone. This type of research is Classroom Action Research (PTK). The subjects in this study were 30 students of class X SMA Negeri 10 Bone. Data obtained by field notes, observation sheets, tests, interviews, and photo documentation. Using quantitative and qualitative data. The test result data shows that the average value obtained by students in the first cycle is 50 with a complete score of 20% and 60% and 20% for students who do not participate in writing poetry activities. As for the second cycle, the average value was 81 with a complete score of 90% and an incomplete score of 10%. The percentage increase in completeness from cycle I to cycle II was 31% and classically students get an average score above 75. The results achieved have met the predetermined targets. The increase in the average score is to support learning to write poetry through the PAKEM method with blog media.Keywords: Pakem Method, Media Blog, poetry.